The evolving male: spinner dolphin (Stenella longirostris) ecotypes are divergent at Y chromosome but not mtDNA or autosomal markers. Issue 9 (2nd April 2013) - Andrews, Kimberly R.; Perrin, William F.; Oremus, Marc; Karczmarski, Leszek; Bowen, Brian W.; Puritz, Jonathan B.; Toonen, Robert J.
Abstract The susceptibility of the Y chromosome to sexual selection may make this chromosome an important player in the formation of reproductive isolating barriers, and ultimately speciation. Here, we investigate the role of the Y chromosome in phenotypic divergence and reproductive isolation of spinner dolphin (Stenella longirostris) ecotypes. This species contains six known ecotypes (grouped into four subspecies) that exhibit striking differences in morphology, habitat and mating system, despite having adjacent or overlapping ranges and little genetic divergence at previously studied mtDNA and autosomal markers. We examined the phylogeographic structure for all six ecotypes across the species range (n = 261, 17 geographic locations) using DNA sequences from three Y chromosome markers, two maternally inherited mitochondrial (mtDNA) markers, and a biparentally inherited autosomal intron. mtDNA and autosomal analyses revealed low divergence (most ΦST values <0.1) between ecotypes and geographic regions, concordant with previous studies. In contrast, Y intron analyses revealed fixed differences amongst the three most phenotypically divergent groups: S. l. longirostris vs. S. l. roseiventris vs. combined S. l. orientalis/S. l. centroamericana/Tres Marias ecotypes). Another ecotype (whitebelly), previously postulated to be a hybrid between the two phenotypically most divergent ecotypes, had Y haplotypes from both putative parent ecotypes, supporting a hybrid designation. Reduced introgression of the Y chromosome has previously been observed in other organisms ranging from insects to terrestrial mammals, and here we demonstrate this phenomenon in a marine mammal with high dispersal capabilities. These results indicate that reduced introgression of the Y chromosome occurs in a wide taxonomic range of organisms and support the growing body of evidence that rapid evolution of the Y chromosome is important in evolutionary diversification.